2014
DOI: 10.1074/jbc.m114.563114
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor E2-related Factor-2 (Nrf2) Is Required for NLRP3 and AIM2 Inflammasome Activation

Abstract: Background: A subgroup of the NLR (nucleotide binding domain, leucine-rich repeat-containing) proteins and a non-NLR protein AIM2 are key mediators of the inflammasome. Results: Cells lacking Nrf2 are defective in the activation of the NLRP3 and AIM2 inflammasome but not the NLRC4 inflammasome. Conclusion: Nrf2 is an essential mediator of NLRP3 and AIM2 inflammasome activation. Significance: Nrf2 plays a proinflammatory role by enhancing inflammasome activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
115
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(130 citation statements)
references
References 52 publications
14
115
1
Order By: Relevance
“…In this study, we found that Nrf2 activation inhibited NLRP3 inflammasome activation by decreasing ROSinduced NLRP3 transcription. Our in vivo study showed that Nrf2 -/-mice are more susceptible to peritonitis than wild-type mice, which does not agree with a recent study by Zhao et al indicating that Nrf2 -/-mice have significantly less recruitment of immune cells and are less susceptible to peritonitis (51). Aluminduced peritonitis is regarded as a typical NLRP3-IL-1b axis-dependent inflammation animal model, and notably, the dose of alum and its stimulation time influence immune cell recruitment in the peritoneal cavity.…”
Section: Il-1b Was Detected By Elisa (D) Wt Bmdms and Nrf2contrasting
confidence: 51%
“…In this study, we found that Nrf2 activation inhibited NLRP3 inflammasome activation by decreasing ROSinduced NLRP3 transcription. Our in vivo study showed that Nrf2 -/-mice are more susceptible to peritonitis than wild-type mice, which does not agree with a recent study by Zhao et al indicating that Nrf2 -/-mice have significantly less recruitment of immune cells and are less susceptible to peritonitis (51). Aluminduced peritonitis is regarded as a typical NLRP3-IL-1b axis-dependent inflammation animal model, and notably, the dose of alum and its stimulation time influence immune cell recruitment in the peritoneal cavity.…”
Section: Il-1b Was Detected By Elisa (D) Wt Bmdms and Nrf2contrasting
confidence: 51%
“…Considering that Nrf2 modulates CD36 expression in macrophages, Nrf2 may exhibit a pro-atherogenic effect through cholesterol uptake and cholesterol crystal-induced Nlrp3 inflammasome activation. It is also suggested that Nrf2 modulates AIM2 inflammasome activity in addition to the Nlrp3 inflammasome [141].…”
Section: Iron Accumulation Is Observed In Atherosclerotic Lesions Ofmentioning
confidence: 99%
“…The antioxidant transcription factor nuclear factor (erythroidderived-2)-like 2 (Nrf2) represses TXNIP expression in response to oxidative stress (11). However, Nrf2, which is activated by oxidative stress in livers of NASH patients (52), and upregulated in livers of male Wistar rats with fructoseinduced steatohepatitis (60), can also activate NLRP3 inflammasome (61). It is currently unknown whether the ROS-TXNIP pathway or the ROS-Nrf2 pathway is responsible for NLRP3 inflammasome activation in hepatocytes in the context of fructose-induced NAFLD.…”
Section: Introductionmentioning
confidence: 99%